2x^2+9x-5=0
D=b^2-4ac=9^2-4*2(-5)=81+40=121 -корень-11
x1,2= -b+\-корень из D / 2a= -9+\-11 / 4= -5 ; 0,5
(х+3)(5х-3)=05x^2+12x-9=0
D=k^2-ac=6^2-5*(-9)=36+45=81 -корень-9
x1,2= -k+\-корень из D / a= -6+\-9 / 5= -3 ; 0,6
(4у-3)(5-8у) =0-32y^2+44y-15=0 | *(-1) __ 32y^2-44y+15=0
D=k^2-ac=(-22)^2-32*15=484-480=4 -корень-2
x1,2= -k+\-корень из D / a= 22+\-2 / 32= 0,625 ; 0,75
(6а+5)(а-8)=06a^2-43a-40=0
D=b^2-4ac=(-43)^2-4*6(-40)=1849+960=2809 -корень-53
x1,2= -b+\-корень из D / 2a=43+\-53 / 12= -5\6 ; 8
1.х2-5х+8х-40>0 3.х2-30х+25х-750<0
x2+3x-40>0 х2-5х-750<0
Д=3*3-40*4*1=169 Д=-5*-5-4*-750*1=3025
х1=-3+13/2=5 х1=5+55/2=30
х2=-3-13/2=-8 х2=5-55/2=-25
ответ:(5;до бесконечности) ответ:(-25;до бесконечности)
2. х2+10х-14х-140<0
х2-4х-140<0 4.х2-6х+6х-36>0
Д=-4*-4-4*(140)*1=576 x2-36>0
х2=4-24/2=-10 x-6=0 x+6=0
ответ:(-10,до бесконечности) x=6 x=-6 ответ:(6;до бесконечности)